Gender and Diversity Studies in European Perspectives - Hinterhuber, Eva Maria; Vasterling, Veronica (My University, 2015)
Vom 8. bis 10. Januar fand an der Hochschule Rhein-Waal in Kleve die internationale Konferenz „Gender and Diversity Studies in European Perspectives“ statt. Die hier diskutierten Themen reichten von Fragen nach der Umsetzung und dem Wandel von Gender- und-Diversity-Strategien in spezifischen Feldern, Institutionen und europäischen Regionen über stärker theoretisch ausgerichtete Untersuchungen von Diversitäts- und Intersektionalitätskonzepten bis zu Handlungsempfehlungen für zukünftige Schritte. Die Konferenz zeigte die Notwendigkeit auf, die Analyseinstrumente der Gender und Diversity Studies zu schärfen und politische Allianzen über Differenzlinien hinweg auszuhandeln, um Stillstand und Backlash zu überwinden.

The Rhine-Waal University of Applied Sciences in Kleve hosted the international conference on “Gender and Diversity Studies in European Perspectives” from 8 to 10 January 2015. Topics discussed at the conference ranged from the implementation and vicissitudes of gender and diversity policies in specific fields, institutions and European regions, to more theoretical examinations of the concepts of diversity and intersectionality, and proposals for going forward. The conference highlighted the need to sharpen the analytical instruments of gender and diversity studies and to negotiate political alliances across lines of difference in order to overcome stagnation and backlash.
International conference, 8–10 January 2015, Rhine-Waal University of Applied Sciences, Kleve
Keywords: Gender; Intersektionalität; Gleichheit; Diversity Management; 940 Geschichte Europas